(3eaQL GdfaSs - (3eMeO Hf YeQ Hf CHj GdaJhM GdHZOGOj GdeGQOjfj, GHf GdeQGgs
(3ChdgG (B:s
(3aEfi deG WGdYJ CcHQ GdcJH GdWHjI , de CLO ajgG eG jTbi GdbdH ef PcQ GdCehQ s
(3BNQgG (B:s
(3hdMUhd eG jNJGQg hjghGg ef Ci Ufa cGf ef GdhLOGf , aPdc GdMed GdeaQMGf s
(3Vef eLehY s
(3ebSe Edi YTQI CHhGHs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B177 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs